2016
DOI: 10.1680/jgeot.15.p.097
|View full text |Cite
|
Sign up to set email alerts
|

t–z curves for piles from pressuremeter test results

Abstract: Pile design is not only based on the assessment of bearing capacity, but can involve settlement calculations when the structures supported by piles need high service requirements. In this context, the load transfer approach with t-z curve models is one of the calculation methods used. The main issue for this method is the choice and implementation of the t-z curve modelling the behaviour of the soil around the pile and accounting for the progressive shaft friction mobilisation. In this paper, three types of t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The load terms, T and T n , are the same for the three facing limit states, as indicated by the performance functions (i.e., (1), (5), and (6)). This study is focused exclusively on the characterization of T for T n where T n is computed using the default and improved FHWA simplified facing tensile force models.…”
Section: Performance Functions Of Facing Limit Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The load terms, T and T n , are the same for the three facing limit states, as indicated by the performance functions (i.e., (1), (5), and (6)). This study is focused exclusively on the characterization of T for T n where T n is computed using the default and improved FHWA simplified facing tensile force models.…”
Section: Performance Functions Of Facing Limit Statesmentioning
confidence: 99%
“…The quantification of model uncertainty can be done by characterizing the statistics of model bias which is the ratio of measured to nominal value of the variable of interest. Extensive studies on model uncertainty characterization for different geotechnical models have been reported in the literature, e.g., shallow and deep foundations [6][7][8][9][10][11] and retaining structures [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the predictions made by Robas and Kuder [35] and by Said et al [36]-which are the closest predictions to the whole initial part of the measured load-settlement curve-both used the FrankZhao MPM method and were established entirely independently from the raw MPM readings. For categories 9-16, the above values are multiplied by 0.75 when the piles are vibro-driven instead of being driven Research on the use of t-z curves for the assessment of the settlements of piles using the full-scale results of the LCPC pile database has been developed further by Abchir et al [1] and Bohn et al [7].…”
Section: Axial Displacementsmentioning
confidence: 99%
“…In past decades, a number of methods have been developed for pile response analysis, included the theoretical load transfer curve method [2–7], the shear displacement method [812], finite element method [1316], the boundary-element method [1720], the variational approach [2124] and the field test [2527], etc. It is worth mentioning that these studies reported that the pile was surrounded by clay, sand or rock-soil aggregate.…”
Section: Introductionmentioning
confidence: 99%